Clinical Applications of Natriuretic Peptides in Assessment of Valvular Heart Disease. (22nd July 2015) - Sharma, Abhishek; Ahmed, Vaseem; Garg, Aakash; Aggarwal, Chirag
Abstract : Biomarkers such as natriuretic peptides (NPs) have evolving clinical utility beyond the scope of heart failure. The role of NPs in the management of valvular heart disease is a growing area of investigation. NPs have much potential in the assessment of asymptomatic patients with hemodynamically significant valvular lesions who have traditionally been excluded from consideration of surgical intervention. NPs also have a role in the risk stratification of these patients as well as in routine surveillance and monitoring. Together with echocardiographic data and functional status, NPs are being incorporated into the management of valvular heart disease. In this review we examine the evidence for the role of natriuretic peptides in assessment of VHD.